Outcomes in Advanced Head and Neck Cancer Treated with Up‐front Neck Dissection prior to (Chemo)Radiotherapy. (8th October 2015) - Elicin, Olgun; Albrecht, Tobias; Haynes, Alan G.; Bojaxhiu, Beat; Nisa, Lluís; Caversaccio, Marco; Dal Pra, Alan; Schmücking, Michael; Aebersold, Daniel M.; Giger, Roland
Abstract : Objective: Our aim was to compare outcomes with and without up‐front neck dissection prior to (chemo)radiotherapy in head and neck squamous cell carcinoma. Study Design: Case series with chart review. Setting: Tertiary referral center. Subjects and Methods: Outcomes of oropharyngeal, laryngeal, and hypopharyngeal squamous cell carcinoma cases with neck lymph node metastases treated from January 2001 to March 2012 were analyzed. Due to imbalances in baseline characteristics between groups treated with (n = 129) and without (n = 95) up‐front neck dissection, propensity score matching was performed. Results: Median follow‐up was 48 months (range, 12‐148). With up‐front neck dissection, the hazard ratio for the primary end point, disease‐free survival, was 0.63 (95% confidence interval: 0.37‐1.06, P =. 08). Up‐front neck dissection reduced acute grade ≥3 toxicity significantly when xerostomia was excluded (odds ratio: 0.40, 95% confidence interval: 0.20‐0.82, P =. 012). Conclusion: Our results indicate less acute treatment toxicity without any significant difference in terms of oncologic outcome with up‐front neck dissection prior to (chemo)radiotherapy as compared with (chemo)radiotherapy alone. Well‐designed randomized trials are required to verify this result and further investigate the impact of this strategy on late toxicity and oncologic outcome.